Delayed patch repair of a ruptured mitral subvalvular pseudoaneurysm caused by infective endocarditis: a case report. Issue 4 (17th June 2020) - Hohri, Yu; Yamazaki, Sachiko; Numata, Satoshi; Yaku, Hitoshi
Abstract: Background: Ruptured subvalvular pseudoaneurysm is a rare but significantly fatal complication of infective endocarditis. We report a successful surgical case of ruptured subvalvular pseudoaneurysm with infective endocarditis. Case summary: A 46-year-old man presenting with high fever was admitted to a local hospital. Physical examination revealed small erythema and petechiae on his lower limbs. Transthoracic echocardiogram did not show any visible vegetation and valvular disease; however, magnetic resonance imaging (MRI) showed multiple acute cerebral infractions, and methicillin-susceptible Staphylococcus aureus was detected in the blood culture. Infective endocarditis was suspected, and an antibacterial medication was initiated. Twelve days later, he suffered from a sudden cardiogenic shock due to cardiac tamponade. Bloody pericardial effusion (1600 mL) was drained, and his condition improved substantially. Transoesophageal echocardiography after pericardial drainage revealed severe mitral regurgitation and a subvalvular aneurysm at the posteromedial side of the mitral annulus; these were not detected at the time of admission. He was transferred to our hospital for surgery; however, since fresh cerebral bleeding was observed in MRI, the surgery was delayed. Three weeks later, after confirming that the blood culture was negative for any growth, patch repair of the subvalvular pseudoaneurysm and mitral valve repair were performed. Post-operatively, no complication or arrhythmia was observed; he was discharged 25 days later. Discussion: We report a rare case of successful delayed surgery for a ruptured subvalvular pseudoaneurysm at the posteromedial side of the mitral annulus, which presented complications for infective endocarditis by S. aureus .